Roland Barthes at the Collège de France. - O'Meara, Lucy. (Liverpool : Liverpool University Press, 2013)
A full-length account of Barthes' lecture courses given in Paris,1977-80, placing his teaching within institutional, intellectual and personal contexts. Analysing texts and recordings of the four lectures together with his 1970s output, it brings together all the strands of Barthes' activity as writer, teacher and public intellectual.
Cover -- Half-title -- Title page -- Copyright page -- Contents -- Acknowledgements -- Note on Abbreviations and References -- Introduction -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Afterword -- Appendix -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books